2009
DOI: 10.1080/13639080802709653
|View full text |Cite
|
Sign up to set email alerts
|

International student‐workers in Australia: a new vulnerable workforce

Abstract: In the period immediately preceding the 2007 Australian election, much attention was accorded to the impact of the nation's labour laws on vulnerable employees. This debate centred on specific groups including women, youth, migrants and workers on individual employment contracts. International students, by contrast, were ignored in the debate. This omission reflects the fact that though three million students study outside their home country, this community has not previously made an appearance in the labour s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 14 publications
5
85
0
2
Order By: Relevance
“…Vulnerability to exploitation by employers, intermediary agents, education providers and other actors has emerged as a common issue across most temporary visa categories in Australia (see, for example, Biao 2007;Nyland et al 2009;Bertone 2013, 179;Velayutham 2013;Boese et al 2013;Robertson 2015;Berg 2016;Tham et al 2016). Immigration policy settings, such as the increased emphasis on employer-sponsorship in the permanent skilled migration program, can condition pathways between visas in ways that exacerbate migrant precarity by increasing dependence on employers (Productivity Commission 2015, 382-3).…”
mentioning
confidence: 99%
“…Vulnerability to exploitation by employers, intermediary agents, education providers and other actors has emerged as a common issue across most temporary visa categories in Australia (see, for example, Biao 2007;Nyland et al 2009;Bertone 2013, 179;Velayutham 2013;Boese et al 2013;Robertson 2015;Berg 2016;Tham et al 2016). Immigration policy settings, such as the increased emphasis on employer-sponsorship in the permanent skilled migration program, can condition pathways between visas in ways that exacerbate migrant precarity by increasing dependence on employers (Productivity Commission 2015, 382-3).…”
mentioning
confidence: 99%
“…This combination of policy mechanisms, designed to attract more students to Australia had, however, an unintended impact on local labour economies. Student visa holders in Australia became a new underclass of worker in the low skilled and service labour economies (Nyland et al 2009). Some of these labour hierarchies also became highly ethnically stratified.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations on student visas around hours worked and the difficulty many students had in finding mainstream employment led to both 'semi-compliance' (Ruhs & Anderson 2010) in the labour market and increased vulnerability of students to exploitation by employers (Nyland et al 2009). These labour market positions did not magically dissipate to make way for skilled roles once students graduated -in fact, there is significant evidence that it was often difficult for former students to gain skilled work (Gribble & Blackmore 2012) and many had to take on any job available in order to repay study debts and finance ongoing living costs (Robertson 2013, Robertson & Runganakailoo 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The study revealed that college and university students are at the highest risk of injury in the workplace. According to Nyland et al, when international students involved in the workplace, the potential hazards and risks exposure due to illegal and unsafe work are even multiplied [19].…”
Section: Health and Safety Of Young Workersmentioning
confidence: 99%
“…Recently, there is a growing number of international students involved in the Australia labor market [19]. However, this sub-group of working population may even more vulnerable compared to their domestic peers [19], [22].…”
Section: Overlapping Vulnerabilitiesmentioning
confidence: 99%